Prague as a Knowledge City-Region - Pechlát, Jakub (Teorie vědy / Theory of Science, 2010)
Prague is well known as political, economic and cultural centre of the country. In recent years, cities and regions are regarded and analyzed as knowledge-based economies. This paper tries to summarize selected data allowing the description of Prague as a knowledge-based regional economy and its development as such in the last decade. Presented are various available indicators together with findings of selected recent innovation-related analyses and data on financial support from EU Structural Funds. Furthermore, this paper introduces city development strategies and explains how they aspire to contribute to the development of the city as a knowledge-based economy.